1998
DOI: 10.1002/(sici)1096-9837(199809)23:9<791::aid-esp888>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Bed material transport estimated from the virtual velocity of sediment

Abstract: This study evaluates the possibility of determining bed material transport using the virtual rate of travel of individual particles, dimensions of the active layer of the streambed, and porosity and density of streambed material. Magnetically tagged stones and scour indicators were employed in Carnation Creek, British Columbia, to quantify transport rates. Observations cover flows up to 36 m 3 s −1 (τ* = 0·081). Tranport rates, ranging from 0·090 to 9·7 kg s), display a relatively sensitive trend with maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
168
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(181 citation statements)
references
References 28 publications
9
168
3
1
Order By: Relevance
“…29 links the mean residence time of sediment storage and the virtual sediment velocity Vc in each storage component under steady state. The virtual velocity is defined by the total travel distance of the sediment divided by the considered time interval and therefore includes periods of rest and motion (Haschenburger and Church, 1998). To summarize, soil redistribution within the Aufsess catchments is not in equilibrium.…”
Section: Accepted Manuscriptsupporting
confidence: 84%
See 1 more Smart Citation
“…29 links the mean residence time of sediment storage and the virtual sediment velocity Vc in each storage component under steady state. The virtual velocity is defined by the total travel distance of the sediment divided by the considered time interval and therefore includes periods of rest and motion (Haschenburger and Church, 1998). To summarize, soil redistribution within the Aufsess catchments is not in equilibrium.…”
Section: Accepted Manuscriptsupporting
confidence: 84%
“…In contrast to Lc, Vc is much more difficult to estimate. Due to the episodic transport of sediment during single events and the short travel distances of sediment during these events, the characteristic velocity incorporates both periods of motion and rest, between successive transport events (Haschenburger and Church, 1998). Thus, Vc depends on the frequency of the transport events and the mean travel distances of the sediment during these events.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…At the smallest relevant scales of turbulence, the threshold of motion is determined by the impulse, the product of shear stress magnitude, and duration (Diplas et al, 2008). Due in part to the difficulties in measuring tracer particle motion and near-bed stresses during floods, the fluid shear stress is commonly quantified through use of a bulkflow parameter such as the depth-slope product, τ b = ρg h S (Church and Hassan, 1992;Hassan et al, 1991;Ferguson and Wathen, 1998;Haschenburger and Church, 1998;Lenzi, 2004;Haschenburger, 2011), where h is the flow depth (m) and S is channel slope. For coarse-grained streams this simplification is perhaps more reasonable, as particle inertial timescales are large and thus coarse particles are insensitive to a range of turbulent stress fluctuations (Diplas et al, 2008;Celik et al, 2010;Valyrakis et al, 2010Valyrakis et al, , 2013.…”
Section: Dimensionless Impulsementioning
confidence: 99%
“…Tracer particles have thus been used, both in the field and in laboratory experiments, to quantify bedload entrainment at a fixed location (Reid et al, 1985;Wilcock, 1997), the travel distance of a single particle (Ferguson and Wathen, 1998;Martin et al, 2012), or particle storage in the sediment bed (Haschenburger and Church, 1998). Most studies revealed right-skewed and fat-tailed distributions of the travel distance.…”
Section: Introductionmentioning
confidence: 99%